2018
DOI: 10.1521/pedi_2017_31_295
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Schema Coping Inventory and Schema Mode Inventory in Adolescents

Abstract: This study investigated whether the schema therapy constructs of schema coping and schema modes have val dity in adolescents. We examined the validity and reliability of the Schema Coping Inventory (SCI) and an 80-item version of the Schema Mode Inventory (SMI) in a mixed sample of adolescents. Confirmatory factor analyse showed that the first-order factor structures of the SCI and SMI were replicated, but that the hypothesized higher-order models of the SMI were not confirmed. Instead, we proposed an alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…The healthy adult and happy child modes were observed to have a negative correlation with the unhealthy modes while having a positive and significant correlation with the other modes. These results are consistent with earlier studies (Lyrakos, ; Panzeri et al, ; Reiss et al, ; Van Wijk‐Herbrink et al, ).…”
Section: Conclusion Discussion and Suggestionssupporting
confidence: 93%
See 1 more Smart Citation
“…The healthy adult and happy child modes were observed to have a negative correlation with the unhealthy modes while having a positive and significant correlation with the other modes. These results are consistent with earlier studies (Lyrakos, ; Panzeri et al, ; Reiss et al, ; Van Wijk‐Herbrink et al, ).…”
Section: Conclusion Discussion and Suggestionssupporting
confidence: 93%
“…In the social sciences, it has been noted that acceptable internal consistency values are.60 and above (Büyüköztürk, ). When compared with the results of the scale's validity and reliability studies in other cultures, the results of this study were parallel to those of other studies (Lyrakos, ; Panzeri et al, ; Van Wijk‐Herbrink et al, ). In addition, as part of reliability studies, the scale's test–retest values were analysed.…”
Section: Conclusion Discussion and Suggestionssupporting
confidence: 85%
“…We asked the participants to rate to what extent (on a 6-point measurement scale; from 1 ¼ not at all, to 6 ¼ very much so) they experienced these emotions at that moment. Studies have shown adequate psychometric properties of the SMI in both adults and adolescents (Roelofs et al, 2016;van Wijk-Herbrink, Roelofs, et al, 2018;Young et al, 2007). In the current sample, internal consistencies for anger and feelings related to abandonment and abuse were good: Cronbach's alphas for anger were 0.82 at T 0 and 0.91 at T 1 , and Cronbach's alphas for feelings related to abandonment and abuse were 0.93 at T 0 and 0.94 at T 1 .…”
Section: Early Maladaptive Schemasmentioning
confidence: 99%
“…For example, the Abandonment schema (i.e., the belief that others will abandon you when you start to attach to them) may activate feelings of anger when abandonment is perceived as unfair or as betrayal. Indeed, one study showed that schemas of the disconnection and rejection domain, including the Abandonment schema, were associated with adolescents' oppositional and aggressive behaviors (van Wijk-Herbrink, Roelofs, et al, 2018).…”
mentioning
confidence: 99%
“…Most studies examining modes have utilized the Schema Mode Inventory, a retrospective self-report instrument (for reviews, see Lobbestael et al, 2010;Sempértegui, Karreman, Arntz, & Bekker, 2014). Using this measure, modes have largely been found to relate to PDs in theoretically coherent ways (e.g., van Wijk-Herbrink et al, 2018).…”
Section: The Present Studymentioning
confidence: 99%